Climate impact on Alternaria moulds and their mycotoxins in fresh produce: The case of the tomato chain. (February 2015) - Van de Perre, Evelien; Jacxsens, Liesbeth; Liu, Cheng; Devlieghere, Frank; De Meulenaer, Bruno
Abstract: Climate change will affect the presence and concentration of mycotoxin in various foods. Recently, a concern arised on the presence of Alternaria mycotoxins in tomatoes and derived tomato products. The objective of this study was to evaluate the effect of climate change on their growth and mycotoxin production on tomatoes in function of changing temperatures. Therefore, a climate change model "HadGEM2-ES" was applied and downscaling of coarse gridded data was done towards a tomato field surface. After transforming the daily temperature data towards hourly data, the growth model of the Alternaria mould was applied. This leads to an assessment of growth rate and actual growth for three time frames being current (1981–2000), near (2031–2050) and far future (2081–2100). The influence of the harvesting period in a growing season, RCP scenarios and time frames was evaluated and two regions, Spain and Portugal were compared with each other. For Spain there were no significant differences for RCP 2.6 and 4.5. For the more extreme RCP scenarios (6.0 and 8.5) the diameter of the mould was significantly lower for the far future compared with the current time frame. This can be explained by the higher temperatures (18.2–38.2 °C) which become too high for fungal growth. For Poland, there was a significant difference in the different time frames, the diameter of the mould was for the far future > near future > current time frame. This is due to the predicted higher temperatures in the far future (14.2–28.4 °C) which becomes closer to the optimal temperature for the growth of Alternaria spp. compared with the colder temperatures in the present. According to the results, the situation in Poland in the far future (2081–2100) will became similar as the situation in Spain in the present time frame (1981–2000). Highlights: Evaluating effect of climate change on growth and mycotoxin production on tomatoes in function of changing temperatures For Spain, for RCP 6.0 and 8.5 the diameter of the mould was significantly lower for the far future then current time frame For Poland, the diameter of the mould was for the far future>near future>current time frame The situation in Poland in the far future will became similar as the situation in Spain in the present time frame